Guidelines for reporting research using systematic coding of observed human behaviour (SCOBe) - Hillen, Marij A.; Hoeben, Evelien M.; Kok, Rianne; McHale, Calum; Sexton, Melissa M.; van der Asdonk, Sabine; van de Bongardt, Daphne; Bowman, Brett; Brown, Richard; Branje, Susan; Chorney, Jill; Donker, Monika H.; et al. (Quality & quantity, 2025)
Systematic coding of observed human behaviour (SCOBe) is used across disciplines and topics but methodological reporting is often incomplete. We developed internationally generated, interdisciplinary guidelines for methodological reporting of such research. Using Delphi methodology, a working group of 22 experts sought group consensus in three rounds. Participants first assessed an initial set of reporting criteria (round 1). Next, in interactive meetings participants revised these criteria and reached consensus on reporting content (rounds 2 & 3). We present 20 criteria constituting the first comprehensive reporting guidelines for SCOBe research using existing, newly developed, or modified coding systems. The criteria encompass three procedural domains: 1. Research context; 2. Properties of the coding scheme; and 3. Application of the coding scheme. The presented guidelines will assist in substantiating and assessing the quality of SCOBe research. We encourage researchers to adopt these guidelines, to enhance quality of mono- and interdisciplinary research.